Law and moral licensing in Canada: the making of illegality and illegitimacy along the border. (24th September 2019) - Labman, Shauna; Liew, Jamie Chai Yun
The thousands of migrants crossing the Canadian land border irregularly are challenging the nature of law and the role the law plays at and around, the border. Likewise, the thousands of refugees who enter Canada each year through resettlement are framed within the validity of their legal arrival across the border. The article addresses the perceived notion that there is a singularity of the law along the border that informs which migrant is 'legal' or 'illegal'. We examine the refugee system in Canada to illustrate the various layers that influence the normative discourse on refugee protection. We reveal a tension in rendering persons rhetorically legal or illegal not by whether a person is in need of protection but by the means through which persons seek that protection. This article seeks to understand how this tension is tied to and, buoyed by, moral licensing whereby application of the 'illegal' refugee concept, combined with the self-congratulation surrounding Canada's resettlement activities, act together to empower a moral comfort with slackened support for refugees seeking asylum.